2,2-Dimethyl-N,N′-bis(4-nitrobenzylidene)propane-1,3-diamine - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title compound, C(19)H(20)N(4)O(4), a potential bidentate Schiff base ligand, each imino (C=N) functional group is coplanar with the adjacent benzene ring. The two benzene rings form a dihedral angle of 10.52 (6)°. Intermolecular C—H⋯O contacts link neighbouring molecules into supramolecular array with an R (2) (2)(32) ring motif and a C—H⋯π contact is also present.